2021
DOI: 10.1002/hpm.3296
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 calls for health systems strengthening in Africa: A case of Nigeria

Abstract: The COVID‐19 pandemic has proven the need for countries worldwide to implement strategies that promote health systems strengthening and ensure epidemic preparedness. Many African countries are burdened by fragile healthcare systems, hence, this paper emphasises the need for African policymakers to improve healthcare quality in their countries. Through a brief review of various online literatures concerning health systems strengthening in Africa, this paper focuses on the nature of healthcare in Nigeria amidst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…63,98 Low health workforce and limited health facilities are also contributing indirectly to weak COVID-19 surveillance in Africa. [98][99][100] It is therefore important that the African government should continue to combat this defiance in order to improve the overall healthcare systems on the continent.…”
Section: Weak Healthcare Systemsmentioning
confidence: 99%
“…63,98 Low health workforce and limited health facilities are also contributing indirectly to weak COVID-19 surveillance in Africa. [98][99][100] It is therefore important that the African government should continue to combat this defiance in order to improve the overall healthcare systems on the continent.…”
Section: Weak Healthcare Systemsmentioning
confidence: 99%
“…However, these figures might still not be the real figures due to the weak national healthcare infrastructures in detecting all cases and also due to many people abandoning reporting in fear of being stigmatized by their infection. In fact, COVID-19 has amplified problems of the fragile health care systems in Africa—a continent that has been found unprepared to deal with this pandemic (Elebesunu et al, 2021 ).
Fig.
…”
Section: Results: Assessing and Outlining The Distinctive Covid-19 Ca...mentioning
confidence: 99%
“…At the same time, evidence shows that malnutrition and lack of food access have aggravated the health crisis (Mertens & Peñalvo, 2021 ). Therefore, more efforts and rigid preliminary healthcare plans are important to save citizens’ life, especially the vulnerable groups like children, pregnant women, old people and patients with chronic diseases (Dasgupta & Robinson, 2021 ; Elebesunu et al, 2021 ). COVID-19 has also shown that these efforts need to incorporate sustainable and more comprehensive approaches such as One Health strategies addressing multi-sectoral and multidisciplinary health issues, i.e., linking human health to environmental and animal healths (Ayobami et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPPs can play an essential role in LMICs health system strengthening 9 , particularly during outbreaks and epidemics, where a coordinated, rapidly scalable approach is required. Strengthening and coordination of public and private health systems is needed to ensure progress towards UHC and global health security 18 . The challenge is to combine private and public efforts in healthcare delivery in a mutually supportive and collaborative manner.…”
Section: Introductionmentioning
confidence: 99%